Study on Twisted Product Almost Gradient Yamabe Solitons. (13th May 2021) - Kim, Byung Hak; Choi, Jin Hyuk; Lee, Sang Deok
Abstract : In this paper, we first study gradient Yamabe solitons on the twisted product spaces. Then, we classify and characterize the warped product and twisted product spaces with almost gradient Yamabe solitons. We also study the construction of almost gradient Yamabe solitons in the Riemannian product spaces.